1999
DOI: 10.1097/00005176-199901000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microflora in Healthy Infants Born by Different Methods of Delivery: Permanent Changes in Intestinal Flora After Cesarean Delivery

Abstract: This study shows for the first time that the primary gut flora in infants born by cesarean delivery may be disturbed for up to 6 months after the birth. The clinical relevance of these changes is unknown, and even longer follow-up is needed to establish how long-lasting these alterations of the primary gut flora can be.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
535
6
38

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 780 publications
(603 citation statements)
references
References 31 publications
24
535
6
38
Order By: Relevance
“…We observed that children born by Caesarean section tended to be obese, although this result did not reach statistical significance. Past studies have found that Caesarean section delivery increases the risk of obesity (Goldani et al ., 2011; Mueller et al ., 2015; Portela et al ., 2015) and impacts the infant gut microbiota (Grönlund et al ., 1999). In our study, delivery mode and infant feeding history (breast‐fed vs. formula‐fed) were not significantly associated with obesity or the gut microbiota composition of children (mean age = 11).…”
Section: Discussionmentioning
confidence: 99%
“…We observed that children born by Caesarean section tended to be obese, although this result did not reach statistical significance. Past studies have found that Caesarean section delivery increases the risk of obesity (Goldani et al ., 2011; Mueller et al ., 2015; Portela et al ., 2015) and impacts the infant gut microbiota (Grönlund et al ., 1999). In our study, delivery mode and infant feeding history (breast‐fed vs. formula‐fed) were not significantly associated with obesity or the gut microbiota composition of children (mean age = 11).…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiota are thought to play an important role in stimulating the development of the immune system [48]. Recent studies have shown that the gut microbiotic composition differ in children born by Caesarean section compared with vaginally born children [8][9][10][11], perhaps because such children are first exposed postpartum to bacteria originating from the hospital environment rather than to maternal bacteria [11]. This difference in gut microbiotic composition could increase the risk of type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Animal models suggest a higher risk of diabetes after Caesarean section [6,7]. Also, children delivered by Caesarean section have been shown to have altered gut microbiotic composition and immune function [8][9][10][11], which could increase their risk of type 1 diabetes. Numerous studies have investigated Caesarean section and type 1 diabetes, but findings have been inconsistent, possibly as a result of inadequate size and limited power in some studies.…”
Section: Introductionmentioning
confidence: 99%
“…Ainsi, l'enfant né par voie basse est d'abord colonisé par des bactéries d'origine maternelle, en particulier des bactéries vaginales, fécales ou cutanées [3]. Ensuite, les intestins du nouveau-né sont rapidement colonisés par les bactéries de l'environnement, essentiellement des Escherichia coli et des streptocoques, puis par celles contenues dans son alimentation, à base de lait, notamment les bifidobactéries et les lactobacilles.…”
Section: Installation Du Microbioteunclassified